Pelatihan, Produksi, Pemasaran Dodol Jagung Khas Paitana bagi Remaja dan Ibu Rumah Tangga di Jeneponto - Sri Prilmayanti Awaluddin; Nurani Nurani; Akbar Awaluddin; Muntasir Muntasir; Nurhikma Awaluddin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Training on corn dodol processing and simple household bookkeeping as an effort to provide added value to products so that they have more economic value to increase community income and welfare, especially for young women, young mothers, and housewives in Paitana Village. Corn harvest results with high nutritional content can be processed into typical Paitana dodol Research: This method includes the Activity Preparation Stage, Activity Implementation, Activity Evaluation and Reporting on program implementation. Carried out in the form of socialization, lectures, questions and answers and product manufacturing practices Results: The results of the activity show the support and desire of the community, especially young women, mothers, and housewives who are PKK members in Paitana village enthusiastically participating in this training. There were 25 young women, mothers, and housewives. To understand the importance of processing lokal corn food to produce dodol products with high nutritional and economic value that can be sold on the market. Understanding the importance of marketing lokal Paitana corn dodol food-processing products with economic value. understand the importance of simple bookkeeping and household financial reports, so that business bookkeeping and household financial records can be carried out with business financial records. Limitations: Limited facilities and infrastructure, and participants who attended are limited to 25 people, as proposed. The packaging is still done using a simple design, and the dodol produced has not been marketed because it is still on a household training scale and there is no business permit. Contribution: This service is beneficial for the community, which processes the lokal potential of the region into family income and improves the community's economy.